2018
DOI: 10.1007/s11356-018-2486-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the dynamics of heavy metals in saline wastewater treated in constructed wetland mesocosms or microcosms filled with porous slag

Abstract: This study aims to evaluate the practical potential of using constructed wetlands (CWs) for treating saline wastewater containing various heavy metals. The results demonstrated that CWs growing Canna indica with porous slag as substrate could efficiently remove heavy metals (Cu, Zn, Cd, and Pb) from saline wastewater at an electrical conductivity (EC) of 7 mS/cm, especially under low influent load. Salts with salinity level (characterized as EC) of 30 mS/cm suppressed the removal of some heavy metals, dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…2 ). These results match those observed in earlier studies, especially in hydroponic conditions (Cheng et al 2012 ; Liang et al 2019 ). Such decreased uptake at high salinity has been explained by lower availability (Costa et al 2020 ), competition between uptake sites (Bond et al 1988 ), and increased exclusion capacity (Mahon and Carman 2008 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 ). These results match those observed in earlier studies, especially in hydroponic conditions (Cheng et al 2012 ; Liang et al 2019 ). Such decreased uptake at high salinity has been explained by lower availability (Costa et al 2020 ), competition between uptake sites (Bond et al 1988 ), and increased exclusion capacity (Mahon and Carman 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…Decreased heavy metal removal under saline conditions has earlier been found in biofilters, constructed wetlands, and floating wetlands (Huang et al 2017;Liang et al 2019;Szota et al 2015). This indicates a wider problem with heavy metal removal in plant-based systems under saline conditions, which may limit their usefulness under such circumstances.…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al [13] used the vertical subsurface flow CWs to purify the wastewater containing Cd, and found that the removal rate of NO 3 -N and Cd 2+ in the wetland reached more than 80%. Liang et al [14] used the porous slag CWs to treat the saline wastewater containing various heavy metals. The results showed that the CWs were effective for treatment of Cu, Zn, Cd, and Pb in the wastewater, and could enhance the enrichment effect of plants on heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater contains pollutants, such as nitrogen and phosphorus may cause algal blooms if discharged into natural water without treatment (Resende, Nolasco, & Pacca, 2019; Rittmann, Mayer, Westerhoff, & Edwards, 2011). Mariculture tailwater also has high salinity and organic matter content, making its biological treatment more challenging (Fu, Han, Yu, Huangshen, & Zhao, 2019; Liang et al, 2018; Vymazal, 2014).…”
Section: Introductionmentioning
confidence: 99%